2020
DOI: 10.7146/torture.v30i1.105661
|View full text |Cite
|
Sign up to set email alerts
|

Parrilla urethra: A sequalae of electric shock torture to genitals in men. A 40 case series in Kashmir (India)

Abstract: Introduction: Since the 20th century, electric shock torture has become one of the most prevalent methods of torture partly because it produces sequelae that are more challenging to visibly detect, particularly when administered using high voltage and low current. In sexual torture, a wire is wrapped around the head of the penis and a wire electrode is inserted into the urethra.This produces unbearable pain and can lead to urethral strictures with devastating physical and psychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…A total of 9937 article titles and abstracts were screened, 1739 full-text articles were assessed, and 266 articles were included for analysis (eFigure 1 in Supplement 1). One article was published in 1947 and the rest in 1977 to 2021, with an average increase of 0.25 additional articles published per year from 1977 ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 9937 article titles and abstracts were screened, 1739 full-text articles were assessed, and 266 articles were included for analysis (eFigure 1 in Supplement 1). One article was published in 1947 and the rest in 1977 to 2021, with an average increase of 0.25 additional articles published per year from 1977 ...…”
Section: Resultsmentioning
confidence: 99%
“…Reports of torture could be identified for an average of 2.1 (95% CI, 1.6-2.6) countries per study, and the range was 0 to 39 countries. Only 1 country of torture could be identified for 143 studies (54%), 2 to 10 countries for 53 studies (20%), more than 10 countries for 11 studies (4%), and no single country of torture could be identified for 59 studies (22%) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In such scenarios, the electric shock is usually applied to sensitive areas like nipples, anus, and genitals. In particular, the Parrilla urethra is a technique in which a wire is wrapped around the head of the penis, and a wire electrode is inserted into the urethra [16]. The consequences of using electric techniques as a method of torture can vary from electric burns to the death of the victim.…”
Section: Discussionmentioning
confidence: 99%